(untitled) (Research, Society and Development, 2018)
The objective of this study was to investigate the antioxidant consumption and nutritional status of aging. This is a literature review of the integrative type, where a total of ten articles were obtained, in which a detailed analysis of the studies available in full was made in the Scielo, PubMed and EbescoHost databases of the last five years, in Portuguese and English, the following descriptors were used: elderly, food consumption, antioxidants and nutritional status. In the selected studies there was a predominance of insufficient consumption of antioxidant nutrients by the elderly. Regarding nutritional status, it was possible to notice the predominance of overweight in this public. It is possible to consider a relationship between the nutritional status and the food consumption of antioxidants in the elderly, however, it is necessary to carry out further studies in order to elucidate the present theme.